Power consumption control of LEDs considering their specific characteristics and ambient temperature variations. (July 2019) - Kalani, Mohammad Javad; Salay Naderi, Mehdi; B. Gharehpetian, Gevork
Abstract: Ambient temperature is one of the factors affecting the luminous flux and the lifetime of LEDs. To consider this factor, In this study, the design and implementation of an innovative power control system of LEDs is presented. The distinct feature of the proposed system is its ability to use the information of the ambient temperature and the specific characteristic curves of LEDs. In the proposed method, a microcontroller unit controls the input power of the LED chipsets just by using the instant measured ambient temperature data, if the instant power is higher than the standard power (at 25 °C). The introduced system adjusts the input power and the light output of LEDs at temperatures below the standard ambient temperature of 25 °C. At the same time, this system preserves the standard lighting levels unchanged. Results of the calculations and implementation of the proposed system verify the efficiency of the developed method.